Empty Ocean. - Ellis, Richard (Island Press, 2004)
In The Empty Ocean, acclaimed author and artist Richard Ellis tells the story of our continued plunder of life in the sea and weighs the chances for its recovery. Through fascinating portraits of a wide array of creatures, he introduces us to the many forms of sea life that humans have fished, hunted, and collected over the centuries, from charismatic whales and dolphins to the lowly menhaden, from sea turtles to cod, tuna, and coral. Rich in history, anecdote, and surprising fact, Richard Ellis's descriptions bring to life the natural history of the various species, the threats they face, and the losses they have suffered. Killing has occurred on a truly stunning scale, with extinction all too often the result, leaving a once-teeming ocean greatly depleted. But the author also finds instances of hope and resilience, of species that have begun to make remarkable comebacks when given the opportunity. Written with passion and grace, and illustrated with Richard Ellis's own drawings, The Empty Ocean brings to a wide audience a compelling view of the damage we have caused to life in the sea and what we can do about it."